An FTIR and X‐ray diffraction study of the crystal phase transition in isotactic polybutene‐1. Issue 5 (13th July 2021) - Wen, Huiying; Li, Hongshu; Qiao, Pengfei; Chen, Chunxia; Jiang, Shichun
Abstract: The nature of crystal transformation in the industrially important polyolefin isotactic polybutene‐1 (iPB‐1) with excellent mechanical properties has not been well understood. We investigated the crystal structure transition of iPB‐1 via wide‐angle X‐ray diffraction (WAXD) and Fourier transform infrared spectroscopy (FTIR) after crystallization at 78°C from the melt at 200°C. The total crystallinity index based on the WAXD results and the evolutions of form I and form II according to FTIR spectroscopy were analyzed. It was found that the total crystallinity increases with the transition time, and the time to detect the initiation of the form I is about 20 h but the time for the initiation of the decrease in the form II content is about 50 h. The result indicates that the increase of the crystallinity during the transition originates from the direct formation of the form I rather than the transformation of the form II. These results provide valuable insight into the structure evolution of the iPB‐1 crystal phase transition. Abstract : The Fourier transform infrared spectroscopy results show that the initiation time for form I to increase is much shorter than that for form II to decrease in the crystal transition of iPB‐1 after melting crystallization. The evolution of the total crystallinity is consistent with the increasing rate of form I during the transition and the excess increasing of total crystallinity originates from the direct formation of form I rather than the fresh formation of form II and then transforms to form I.